2006
DOI: 10.1016/j.physd.2006.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Multistable solitons in the cubic–quintic discrete nonlinear Schrödinger equation

Abstract: We analyze the existence and stability of localized solutions in the one-dimensional discrete nonlinear Schrödinger (DNLS) equation with a combination of competing self-focusing cubic and defocusing quintic onsite nonlinearities. We produce a stability diagram for different families of soliton solutions, that suggests the (co)existence of infinitely many branches of stable localized solutions. Bifurcations which occur with the increase of the coupling constant are studied in a numerical form. A variational app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 51 publications
6
87
0
Order By: Relevance
“…Very recently, similar predictions have been made for other nonlinear media, for example in cubic-quintic systems [26] and for localized surface waves [27].…”
supporting
confidence: 67%
“…Very recently, similar predictions have been made for other nonlinear media, for example in cubic-quintic systems [26] and for localized surface waves [27].…”
supporting
confidence: 67%
“…12(b) features a loop, which is a characteristic feature of the SSB in models with saturable [22] and CQ nonlinearities. In the latter context, closed bifurcation loops were found in the discrete (lattice) version of the CQ model [31], and in a system of two linearly coupled NLS equations with the CQ nonlinearity [32]. The presence of the bifurcation loop implies that the broken symmetry is eventually restored, under the action of the quintic term.…”
Section: A Strong Couplingmentioning
confidence: 99%
“…Recently, localized states in this one-dimensional discrete model with the competing nonlinearities were studied in detail in Ref. [13], where it was shown that novel classes of solutions can be introduced by this competition.…”
Section: Introductionmentioning
confidence: 99%